2000
DOI: 10.1002/(sici)1099-0518(20000101)38:1<90::aid-pola12>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of carbazole derivatives in cationic polymerization with a novel sensitivity to near-UV light

Abstract: Photosensitizers based on the carbazole structure were designed and developed for cationic polymerization. Along with triarylsulfonium and diaryliodonium salts, the carbazole derivatives showed a high photosensitization effect in the cationic photopolymerization of epoxides. The photophysical properties of the carbazole derivatives were studied in terms of electronic absorption, fluorescence, and phosphorescence spectrometry. Moreover, a unique photosensitization mechanism of the carbazole derivatives was disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 20 publications
(18 reference statements)
1
42
0
Order By: Relevance
“…We have reported extensively on our studies in this area 2 ' 3,4 and other investigators have also been active in this field. 5,6,7,8 There are several mechanisms by which the photosensitization of onium salts take place, however, electron-transfer photosensitization appears to be the most efficient and generally applicable process. 9 A generalized mechanism for the electron-transfer photosensitization of diaryliodonium salts is shown in Scheme 1.…”
Section: Ptmentioning
confidence: 99%
“…We have reported extensively on our studies in this area 2 ' 3,4 and other investigators have also been active in this field. 5,6,7,8 There are several mechanisms by which the photosensitization of onium salts take place, however, electron-transfer photosensitization appears to be the most efficient and generally applicable process. 9 A generalized mechanism for the electron-transfer photosensitization of diaryliodonium salts is shown in Scheme 1.…”
Section: Ptmentioning
confidence: 99%
“…Figure 8 shows the UV–visible absorbance spectra of pure PNVC and PCN materials in THF solutions. There are two absorbance bands observed at around 250 and 330 nm that may be attributed to π–π* absorptions of the aromatic chromophores of the carbazole units in the polymer 25. The wavelengths of pure PNVC and PCN materials in the UV–visible regions are gradually affected by the presence of clay loading in the PCN materials as illustrated in Table I.…”
Section: Resultsmentioning
confidence: 99%
“…[12] Previously, we have reported that a wide variety of electron-rich polynuclear aromatic compounds are efficient electron-transfer photosensitizers for all three onium salt cationic photoinitiators (I-III). [13] More recently, Chen et al [14] have described studies of the photosensitized photolysis of onium salts I and II by various compounds containing the carbazole nucleus. We have also reported that 9-vinylcarbazole (NVK), [15] its polymer (poly(9-vinylcarbazole)) and copolymers with other vinyl monomers [16] are excellent electron-transfer photosensitizers for onium salt photoinitiators.…”
Section: Introductionmentioning
confidence: 91%